A preliminary study on the effect of the methods of cutting master gutta percha cone on apical seal - Joson, Ma. Cristina; Legaspi, Editha; Porter, Irene (Adviser).
This in vitro study evaluated the effect of cutting the master gutta percha cone tip on the integrity of the apical seal through autoradiography. Fifty-two newly extracted human maxillary incisors were biochemically prepared and obturated with gutta percha using single cone technique. The first group of teeth were obturated with gutta percha cones cut with scissors and the other group, using cones cut with a sharp Bard Parker blade #15. Results revealed that obturating the teeth using master gutta percha cone cut with the blade allowed less apical seal leakage.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Gutta-percha.; Endodontics